ANALISIS KEBUTUHAN PENGEMBANGAN KOMPETENSI (AKPK) PEGAWAI PUSKESMAS SERPONG 2 TANGERANG SELATAN - Karyadi, Karyadi; Rimadhoni, Ramly Nur; Tryastuti, Dini (NURSE: Journal of Nursing and Health Science, 2023)
ABSTRACT Competency development is an effort to fulfill ASN competency needs. Every ASN has the right to obtain competency development. ASN competency standards are an embodiment of a description of the knowledge, skills, and behavior needed by an ASN in carrying out their duties. This competency includes 3 elements, namely Technical Competence, Managerial Competence, and Socio-Cultural Competence. The aim of this study is to describe Managerial competencies (Integrity, Teamwork, Communication, Orientation on Results, Public Service, Development of self and others, Managing Change, and Decision Making) and Social-Cultural Competence (Perekat Bangsa) to then be analyzed in order to obtain appropriate competence development results for employees. The research method used is Quantitative Descriptive. The sample in this study were 29 respondents with total sampling technique using inclusion criteria. Data were collected using the questionnaire method from the 2017 Permenpan & Rb competency dictionary. The analysis used in this study was univariate analysis. The results showed that there were employees who had not reached the good criteria in Managerial Competency in the category of cooperation with 1 employee, communication with 2 employees, orientation towards results 1 employee, public service with 1 employee, self-development and other people with 2 employees, managing change with 1 Employees and several recommendations for competency development for these employees are training for work team development, training for effective communication, training for organizational performance through learning, training for public services for government agencies, training for self-development and ASN professionalism, and training for adaptability.Keywords: